Comparing ex vivo and in vitro translocation of silver nanoparticles and ions through human nasal epithelium. (July 2018) - Falconer, Jonathan L.; Alt, Jeremiah A.; Grainger, David W.
Abstract: Silver nanomaterials are widely used in clinically approved devices, consumer goods, and over-the-counter nutraceutical products. Despite the increase in silver nanomaterial research, few investigations have specifically distinguished the biological effects resulting from silver nanoparticles (AgNPs) versus silver ions released from AgNPs. This is in part, due to the complex analytical methods required to characterize silver ion release from AgNPs in biological media. This study sought to analyze silver ion release from AgNPs in biological media, compare silver transport from soluble AgNO3 and AgNPs through ex vivo full thickness sinus human tissue explants and human nasal epithelium and determine fractional AgNP internalization by human nasal epithelial cells. Rapid silver ion release is observed from AgNPs in human nasal epithelial cell medium over 3 h (9.6% of total silver mass). Significantly lower translocation of AgNPs is observed through human nasal epithelial cell monolayers and ex vivo human sinus tissue explants compared to silver ion (AgNO3 ). AgNP internalization is directly observed in AgNP-exposed human nasal epithelial cell monolayers by live cell scanning transmission electron microscopy (STEM), providing one potential mechanism for AgNP transcytosis. However, in vitro AgNP dissolution experiments suggest that silver in human nasal epithelium is primarily silver ion. Ionic AgNO3 produces significantly higher silver translocation, supporting previous results claiming silver ion as primarily responsible for biological effects of AgNPs.